2008
DOI: 10.1029/2007ja012787
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and coupled‐channels investigation of the radiative properties of the N2c41Σu+X1Σg+ band system

Abstract: [1] The emission properties of the N 2 c 0 4 1 S u + À X 1 S g + band system have been investigated in a joint experimental and coupled-channels theoretical study. Relative intensities of the c 0

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 99 publications
0
23
0
Order By: Relevance
“…The predissociation efficiency η is then given by η = 1−τ tot /τ rad , where τ tot is the inverse of the sum of the radiative and predissociation rates. For almost all transitions, η 1: significant corrections for partial dissociation are needed only for the b − X(1, 0) and c − X(0, 0) bands near 986 and 959 Å, respectively (Lewis et al 2005b;Liu et al 2008;Sprengers et al 2004;Wu et al 2012). For example, the top panel of Fig.…”
Section: Photoabsorption and Photodissociation Spectrummentioning
confidence: 99%
“…The predissociation efficiency η is then given by η = 1−τ tot /τ rad , where τ tot is the inverse of the sum of the radiative and predissociation rates. For almost all transitions, η 1: significant corrections for partial dissociation are needed only for the b − X(1, 0) and c − X(0, 0) bands near 986 and 959 Å, respectively (Lewis et al 2005b;Liu et al 2008;Sprengers et al 2004;Wu et al 2012). For example, the top panel of Fig.…”
Section: Photoabsorption and Photodissociation Spectrummentioning
confidence: 99%
“…The Viking Lander mission (17,18) measured the Martian atmosphere composition, revealing a very high 15 N isotopic enrichment (1.6 times terrestrial) that was suggested as deriving from dissociative recombination and photolysis of N 2 and preferential gravitational escape of the lighter isotope, 14 N (17,(19)(20)(21)(22)(23)(24)(25)(26). Recent work describing the nitrogen isotopic composition of the atmosphere of Titan has also been modeled to interpret its anomalous molecular nitrogen isotopic composition, which is a factor of two higher than the associated HCN (27).…”
mentioning
confidence: 99%
“…using isotope-specific photodissociation cross sections calculated theoretically by the diabatic coupled-channel Schrödinger equation model (Liu et al 2008). To test the extent to which isotopic self-shielding due to N 2 photoionization could significantly affect the relative photoionization rates of 14 N 2 versus 15 N 14 N, and hence might play a role in determining the isotopic composition of N 2 and nitrogencontaining photochemical products in Titan's atmosphere, the measured cross sections for photoionization of 14 N 2 and 15 N 14 N were included in a one-dimensional (1D) photochemical model of Titan's atmosphere (Yung et al 1984;Liang et al 2007aLiang et al , 2007b.…”
Section: Photochemical Modelmentioning
confidence: 99%